Differing Responses to Phytophthora cinnamomi Infection in Susceptible and Partially Resistant Persea americana (Mill.) Rootstocks: A Case for the Role of Receptor-Like Kinases and Apoplastic Proteases - Backer, Robert; Engelbrecht, Juanita; van den Berg, Noëlani (Frontiers in Plant Science, 2022)
The hemibiotrophic plant pathogen Phytophthora cinnamomi Rands is the most devastating pathogen of avocado (Persea americana Mill.), and as such causes significant annual losses in the industry. Although the molecular basis of P. cinnamomi resistance in avocado and P. cinnamomi virulence determinants have been the subject of recent research, none have yet attempted to compare the transcriptomic responses of both pathogen and host during their interaction. In the current study, the transcriptomes of both avocado and P. cinnamomi were explored using dual RNA-sequencing. The basis for partial resistance was sought through the inclusion of both susceptible (R0.12) and partially resistant (Dusa®) rootstocks sampled at early (6-, 12- and 24- hours post-inoculation; hpi), as well as late time-points (120-hpi). Substantial differences were noted in the number of differentially expressed genes found in Dusa® and R0.12, specifically at 12- and 24-hpi. Here, the partially resistant rootstock perpetuated defense responses initiated at 6-hpi, while the susceptible rootstock abruptly reversed course. Instead, gene ontology enrichment confirmed that R0.12 activated pathways related to growth and development, essentially rendering its response at 12- and 24-hpi no different from that of the mock-inoculated controls. Further analyses revealed that while P. cinnamomi might be switching between its’ biotrophic and necrotrophic life stages at around 24-hpi in Dusa®, in R0.12 the switch seemed to initiate as early as 12-hpi. This was confirmed through earlier expression of several P. cinnamomi effector coding genes known to induce necrosis, when comparing Dusa® and R0.12. Based on some of these observed differences, several P. cinnamomi effectors were highlighted as potential candidates for further research. Similarly, the receptor-like kinase (RLK) and apoplastic protease coding genes in avocado were investigated, focusing on their potential role in the differing rootstock responses. This study suggests that the basis of partial resistance in Dusa® is predicated on its ability to respond appropriately during the early stages following P. cinnamomi inoculation, and that important components of the first line of inducible defense – apoplastic proteases and RLKs – are likely to be essential to the observed outcome.